2021
DOI: 10.1021/acsami.1c14435
|View full text |Cite
|
Sign up to set email alerts
|

Fully Inkjet Printing Preparation of a Carbon Dots Multichannel Microfluidic Paper-Based Sensor and Its Application in Food Additive Detection

Abstract: Microfluidic paper-based sensors as a new type of microsample detection technology are widely used in medical diagnosis, environmental monitoring, and food safety testing. Inkjet printing has the advantages of simplicity, speed, flexibility, high resolution, low cost, and efficient mass production and has become one of the most cutting-edge technologies in the manufacture of paper-based sensors. In this work, a fully inkjet printing preparation method was proposed for paper-based sensors, which can achieve hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Adhesive‐coated foods typically use a mixture of sugar and starch powders with water‐ or alcohol‐based adhesives to create macroscopic and decorative 3D structures (Holland, Foster, et al., 2018). The choice of adhesive is critical in the binder jetting printing through trial and error due to a lack of understanding of the basic interactions that make up a good adhesive (Deng et al., 2021). However, the food printed successfully has a rough appearance and needs further processing (Pitayachaval et al., 2018).…”
Section: Different Innovative Types Of 3d Printing Technologymentioning
confidence: 99%
“…Adhesive‐coated foods typically use a mixture of sugar and starch powders with water‐ or alcohol‐based adhesives to create macroscopic and decorative 3D structures (Holland, Foster, et al., 2018). The choice of adhesive is critical in the binder jetting printing through trial and error due to a lack of understanding of the basic interactions that make up a good adhesive (Deng et al., 2021). However, the food printed successfully has a rough appearance and needs further processing (Pitayachaval et al., 2018).…”
Section: Different Innovative Types Of 3d Printing Technologymentioning
confidence: 99%
“…In terms of chemical modification, covalent chemical modification of paper based on reacting with functional groups in cellulose is the most commonly used method. 56,57 For example, Malancha Gupta et al demonstrated for the first time that solventless initiated chemical vapor deposition can be used for three-dimensional patterning of paper-based microfluidics with a thin layer of hydrophobic photo responsive poly(o-nitro benzyl methacrylate). 58 Hsiu-Yang Tseng et al successfully developed programmable wicking profiles by alternating coated and uncoated zones with a solution composed of potassium alum and animal glue, which is a sizing material used in the fabrication of calligraphy Xuan paper.…”
Section: Papermentioning
confidence: 99%
“…So far, a variety of instrumental techniques for the detection of Fe 3+ have been established, and analytical techniques include chemiluminescence, atomic absorption spectroscopy, fiber‐optic chemical sensors, [5] voltammetry, and inductively coupled plasma mass spectrometry (ICP‐MS) [6] and so on. These instrument technologies have high accuracy and wide detection range for the detection of Fe 3+ , but the disadvantage is the high price of the instrument and the expensive price of subsequent instrument maintenance, time‐consuming pretreatment and tedious operation methods.…”
Section: Introductionmentioning
confidence: 99%